2019
DOI: 10.1002/ghg.1891
|View full text |Cite
|
Sign up to set email alerts
|

A new permeation model in porous filler–based mixed matrix membranes for CO2 separation

Abstract: In this paper, a novel comprehensive permeation model for mixed matrix membranes (MMMs) is introduced. This model shows the importance of understanding and developing a more reliable model for the permeation behavior of MMMs containing porous filler nanoparticles. A new method is established to provide a more precise/large‐scale three‐dimensional MMMs geometry. The required number of spherical porous fillers in random/nonuniform positions in the polymer matrix is calculated. Interfacial equilibrium constant (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 85 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…CO 2 is the most important gas of the earth’s long-lived greenhouse gases, which leads to various problems such as global warming and climate change. With regard to environmental challenges, various separation technologies are considered as commonly applied methods for CO 2 removal such as distillation and cryogenic technologies. Although these methods have high separation efficiencies, they have some drawbacks such as environmental problems, high energy consumption, numerous complicated operation units, and high investment cost. Thus, researchers tried to substitute membrane processes for common technologies, covering the hurdles of previous methods . Membrane processes as a novel and economical technology have different advantages, including low installation costs and energy consumption, high efficiency and stability, and simplicity in scale up and process control; hence they have been able to attract the researchers’ attention. , In recent years, the utilization of polymeric membranes has been widely developed to provide sophisticated gas separation units .…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 is the most important gas of the earth’s long-lived greenhouse gases, which leads to various problems such as global warming and climate change. With regard to environmental challenges, various separation technologies are considered as commonly applied methods for CO 2 removal such as distillation and cryogenic technologies. Although these methods have high separation efficiencies, they have some drawbacks such as environmental problems, high energy consumption, numerous complicated operation units, and high investment cost. Thus, researchers tried to substitute membrane processes for common technologies, covering the hurdles of previous methods . Membrane processes as a novel and economical technology have different advantages, including low installation costs and energy consumption, high efficiency and stability, and simplicity in scale up and process control; hence they have been able to attract the researchers’ attention. , In recent years, the utilization of polymeric membranes has been widely developed to provide sophisticated gas separation units .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, to overcome the limitations of analytical approaches, some authors have proposed numerical models that attempt to consider the real 3D structure of the composite system and that solve the mass transfer using generally, Finite Element Method (FEM). We can cite, as recent examples in that field, the work of Monsalve-Bravo et al [17] who model the three-dimensional (3-D) transport problem in full-scale mixed-matrix membranes using FEM or the work of Sharifzadeh and co-authors (2019) who simulated gas diffusion behavior in 3D composite filled with permeable spherical particles randomly dispersed [18]. The two aforementioned studies confirmed that the permeability is positively correlated to filler volume fraction and particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Fossil fuel combustion leads to the release of the excessive extent of CO 2 into the atmosphere. Global warming appears as an outcome of CO 2 emission into the atmosphere because CO 2 as a greenhouse gas traps the heat 1–5 . Different methods can be employed for CO 2 separation depending on various conditions in the flue gas stream, including cryogenic distillation, pressure swing adsorption, absorption, and membrane process 6–11 …”
Section: Introductionmentioning
confidence: 99%